STRATEGI PENANGGULANGAN KENAKALAN REMAJA DI KELURAHAN BELAWA KECAMATAN BELAWA KABUPATEN WAJO - Najia Angraini; Ramli Ramli; zulfah fakhruddin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
The many problems faced in life that cause a lot of negative access that is very troubling to the community. Access is, among others, increasingly widespread irregularities in the norms of religious and social life that are manifested in the form of juvenile delinquency. The purpose of this study was to find out what forms of juvenile delinquency occurred in Belawa Village, Belawa District, Wajo District. Knowing what strategies are used to overcome juvenile delinquency in Belawa Village, Belawa District, Wajo Regency. Then find out how the influence of juvenile delinquency strategies carried out by the government of Belawa Village, Belawa District, Wajo Regency. This research method uses a qualitative descriptive approach and in data collection using the method of observation, interviews, observing and documentation. As for the data analysis technique used is an inductive analysis technique, meaning that the data obtained in the field is specifically described in words that draw conclusions are general. The results of the study are related to juvenile delinquency coping strategies in Belawa Village, Belawa District, Wajo Regency, namely: (1) Forms of juvenile delinquency that occur in Belawa Village include: racing and recklessness, using glue (fox glue), drinking oplosan ( komix), drinking liquor and drugs (2) The strategy carried out by the police in collaboration with the government of Belawa Village, religious leaders, and the community, including: counseling / socialization, patrolling, raids to sellers, parental attention, planting religious knowledge (3) Efforts to overcome juvenile delinquency committed by the government of Belawa Village, religious leaders, and parents have been maximized. Actions that are preventive ineffective, repressive have been effective and curative have been effective enough to overcome juvenile delinquency.